(untitled) (Proceedings of the International Conference of Geological Engineering Faculty, 2022)
There were two types of hypothesis concerning formation of Makassar Strait and surrounding areas during the Tertiary periods namely, compressive and extensional tectonics. The compression is characterized by formation of Samarinda Anticlinorium in East Kalimantan and West Sulawesi Thrust Fold Belt in Sulawesi whereas the extension was characterized by formation of aulacogen occupied by widening of Mouth of Mahakam River in Makasar Streat and also the presence of block faulting and atenuation on pre Tertiary basement. This study on the basis of analysis new surface and subsurface data of those areas including DEM , Field data and also seismics profiles suggest that the sedimentation cycles and tectonic evolution in the area were simultaneously related to compressional tectonic rather than the extensional tectonics and form flexure subsidence activities. The flexure subsidence itself is related to loading due to tectonic and denudation processes occured in the Tertiarry to Quarternary and this is usually generated during and post collisional activities.